Development and characterization of rabbit monoclonal antibodies that recognize human spermine oxidase and application to immunohistochemistry of human cancer tissues - Tepper, Armand W. J. W.; Chu, Gerald; Klaren, Vincent N. A.; Kalin, Jay H.; Molina-Ortiz, Patricia; Impagliazzo, Antonietta (PLOS ONE, 2022)
The enzyme spermine oxidase (SMOX) is involved in polyamine catabolism and converts spermine to spermidine. The enzymatic reaction generates reactive hydrogen peroxide and aldehydes as by-products that can damage DNA and other biomolecules. Increased expression of SMOX is frequently found in lung, prostate, colon, stomach and liver cancer models, and the enzyme also appears to play a role in neuronal dysfunction and vascular retinopathy. Because of growing evidence that links SMOX activity with DNA damage, inflammation, and carcinogenesis, the enzyme has come into view as a potential drug target. A major challenge in cancer research is the lack of characterization of antibodies used for identification of target proteins. To overcome this limitation, we generated a panel of high-affinity rabbit monoclonal antibodies against various SMOX epitopes and selected antibodies for use in immunoblotting, SMOX quantification assays, immunofluorescence microscopy and immunohistochemistry. Immunohistochemistry analysis with the antibody SMAB10 in normal and transformed tissues confirms that SMOX is upregulated in several different cancers. Together, the panel of antibodies generated herein adds to the toolbox of high-quality reagents to study SMOX biology and to facilitate SMOX drug development.